IDENTIFICATION OF EMISSION LINES IN A METEOR SPECTRUM OBTAINED ON AUGUST 2, 2011 - Mozgova, А. М.; Borovicka, J.; Spurny, P.; Churyumov, K. I. (Одеські астрономічні публікації, 2016)
125 emission lines were found in a meteor spectrum obtained on August 2, 2011. The identification of most of the lines is given. The following species were found in the spectrum: CrI, FeI, MgI, SiI, AlI, MnI, CaI, TiI, NaI, FeII, CaII, MgII, SiII, SrII.